HYDRO-ECOLOGICAL CONDITION OF NATURAL UNDERGROUND SPRING WATERS OF FERGONA CITY (Scientific journal of the Fergana State University, 2024)
Until now, natural underground spring water is also used as drinking water. However, the population does not pay attention to the composition and mineralization of the water they consume. In addition, in places where drinking water does not reach through special lines, underground spring water is consumed. This poses a threat to human health.For this reason, the hydroecological condition of natural underground spring waters distributed in the city of Fergana was studied and analyzed. According to it, the locations of natural underground springs in Fergana city, the history of their occurrence, the size and depth of pits and their GIS map were compiled. In addition, natural underground spring waters were subjected to laboratory analysis and determined whether they are suitable for consumption or not, and in this regard, the state sanitary-epidemiological control center of Fergana region issued reports on water testing in cooperation.In the study of natural underground spring waters, samples were taken and analyzed mainly using observation, comparison, mathematical and laboratory methods.